Influence of magnesium sulfate on HCO3/Cl transmembrane exchange rate in human erythrocytes. (21st March 2016) - Chernyshova, Ekaterina S.; Zaikina, Yulia S.; Tsvetovskaya, Galina A.; Strokotov, Dmitry I.; Yurkin, Maxim A.; Serebrennikova, Elena S.; Volkov, Leonid; Maltsev, Valeri P.; Chernyshev, Andrei V.
Abstract: Magnesium sulfate (MgSO4 ) is widely used in medicine but molecular mechanisms of its protection through influence on erythrocytes are not fully understood and are considerably controversial. Using scanning flow cytometry, in this work for the first time we observed experimentally (both in situ and in vitro ) a significant increase of H C O 3 − /Cl − transmembrane exchange rate of human erythrocytes in the presence of MgSO4 in blood. For a quantitative analysis of the obtained experimental data, we introduced and verified a molecular kinetic model, which describes activation of major anion exchanger Band 3 (or AE1) by its complexation with free intracellular Mg 2+ (taking into account Mg 2+ membrane transport and intracellular buffering). Fitting the model to our in vitro experimental data, we observed a good correspondence between theoretical and experimental kinetic curves that allowed us to evaluate the model parameters and to estimate for the first time the association constant of Mg 2+ with Band 3 as K B 0.07 mM, which is in agreement with known values of the apparent Mg 2+ dissociation constant (from 0.01 to 0.1 mM) that reflects experiments on enrichment of Mg 2+ at the inner erythrocyte membrane (Gunther, 2007 ). Results of this work partly clarify the molecular mechanisms of MgSO4 action in human erythrocytes. The method developed allows one to estimate quantitatively a perspective of MgSO4 treatment for a patient. It should be particularly helpful in prenatal medicine for early detection of pathologies associated with the risk of fetal hypoxia. Highlights: A novel molecular-kinetic model of Band 3 activation by Mg 2+ is introduced. The model is verified experimentally with the use of a scanning flow cytometer. The association constant of Mg 2+ with Band 3 is evaluated as 0.07 mM. The method developed allows quantitative control and optimization of MgSO4 treatment. Results of the work are useful particularly for early detection of risk of hypoxia.